Development of the Consumer Involvement & Engagement Toolkit: a digital resource to build capacity for undertaking patient-centred clinical trials in Australia - Tanya Symons; Janelle Bowden; Anne McKenzie; Julia M Fallon-Ferguson; Leanne Y Weekes; James Ansell; Rinki Murphy; Shilpa Jesudason; Manoj Saxena; Alistair Nichol; Nicola Straiton (Sax Institute, 2023)
Objective: This manuscript describes the novel approach to developing a toolkit to support meaningful consumer involvement in clinical trials in Australia to help guide others in considering the development of similar resources.The toolkit aims to support greater consumer involvement in shaping how clinical research is prioritised, designed and conducted. Type of program or service: A working group of researchers, research organisations and consumers was established to co-develop the Consumer Involvement and Engagement Toolkit (the 'Toolkit'), a digital resource to guide researchers and organisations regarding consumer involvement in clinical trials. Findings: A literature review and international scan of best practice revealed numerous resources outlining best practice for consumer involvement in clinical research and clear evidence of its impact and value. Through a novel content-sharing process, we were able to utilise these resources to develop a comprehensive Toolkit for researchers and research organisations that provides world-class guidance. Lessons learnt: There is a growing movement to ensure consumer involvement in healthcare, including in clinical research. We discovered its proponents were willing to share their tools and resources to promote international consumer involvement. Although these international tools and resources needed adaptation to suit the Australian research environment, this was achievable with far less effort than developing them from scratch.